Electrolyte additive, electrolyte and battery
By using electrolyte additives containing silicon inorganic materials and silicone surfactant in lithium metal batteries, a stable SEI film is formed, which solves the problem of lithium dendrites and improves the cycle performance and safety performance of the battery.
Patent Information
- Application Number
- CN202411707698.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-11-26
AI Technical Summary
Lithium metal batteries are prone to growth of lithium dendrites during charging, resulting in degradation of battery performance and safety hazards. It is difficult for the existing technology to effectively solve this problem.
An electrolyte additive is used, which includes silicon-containing inorganic materials and silicone surfactants. Through these components, a stable SEI film is formed in a lithium metal battery, which promotes the uniform deposition of lithium ions and inhibits the generation of lithium dendrites.
By forming a stable SEI film, the electrolyte additive can significantly inhibit the growth of lithium dendrites and improve the circulation and safety performance of lithium metal batteries.
Smart Images

Figure BDA0005155229360000101 
Figure BDA0005155229360000111 
Figure BDA0005155229360000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to an electrolyte additive, an electrolyte and a battery. Background Art
[0002] In the field of batteries, with the application of high-nickel materials and silicon-carbon composite materials in recent years, the energy density of lithium-ion batteries (LIB) has reached more than 300Wh / kg, which is close to the limit energy density of conventional lithium-ion batteries of 350Wh / kg. There is not much room for further improvement. If lithium-ion batteries want to achieve an energy density of more than 400Wh / kg, new system materials need to be developed. Among them, metallic lithium has a higher theoretical capacity (3860mAh / g) and the lowest electrode potential (-3.04Vvs.H / H + ) and low density (0.534g / cm 3 ), is an ideal negative electrode material for the next generation of high-energy-density batteries.
[0003] In lithium metal batteries (LMBs), the behavior of lithium ions is different from the insertion / extraction behavior of lithium ions in LIBs. During charging of LMBs, lithium ions acquire electrons from the external circuit, and the resulting metallic lithium is deposited on the negative electrode in the form of particles. In LMBs, if the battery system is not improved, it is easy to cause Li + The uneven deposition of lithium ions will produce lithium dendrites, which may lead to electrical short circuits, thermal runaway and other problems in severe cases. In addition, the uneven current density in large currents will make the uneven deposition of lithium ions more serious.
[0004] In the related art, the commonly used methods for inhibiting lithium dendrites mainly include: preparing a three-dimensional skeleton, interface modification engineering and optimization of electrolyte components. These methods can alleviate the growth problem of lithium dendrites to a certain extent, but each of them has certain limiting factors. For example, in the method of preparing a three-dimensional skeleton, the addition of a three-dimensional skeleton will greatly reduce the energy density of the negative electrode material; in the interface modification engineering method, the flexibility, mechanical strength, ionic conductivity and lithium affinity of the interface modification layer are difficult to take into account, and the preparation process is complicated and the uniformity is difficult to ensure. Compared with the method of preparing a three-dimensional skeleton and the interface modification engineering method, the method of optimizing the electrolyte formula is relatively simple and easier to industrialize. However, the existing method of suppressing lithium dendrites by optimizing the electrolyte formula still has problems such as complex operation or difficulty in controlling uniformity, which needs to be further improved. Summary of the invention
[0005] In view of this, the present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides an electrolyte additive, an electrolyte and a battery, which can form a stable SEI film, promote the uniform deposition of lithium ions, and thus help alleviate the growth problem of lithium dendrites.
[0006] In order to solve the above technical problems, this application is implemented as follows:
[0007] According to one aspect of the present application, an embodiment of the present application provides an electrolyte additive, the electrolyte additive comprising a silicon-containing inorganic material and an organosilicon surfactant;
[0008] The organosilicon surfactant includes a hydrophilic group and a hydrophobic group.
[0009] In addition, the electrolyte additive according to the present application may also have the following additional technical features:
[0010] In some of the embodiments, the silicon-containing inorganic material has a particle size of nanometer scale.
[0011] In some embodiments, the silicon-containing inorganic material has a particle size ranging from 5 nm to 50 nm.
[0012] In some embodiments, the silicon-containing inorganic material includes at least one of nano glass powder, nano silicon dioxide, nano silicon oxide, nano silicon element or nano silicon carbide.
[0013] In some embodiments, the hydrophilic group is a group comprising a CO bond, and the hydrophobic group is a group comprising a silicon-oxygen bond.
[0014] In some embodiments, the silicone surfactant includes at least one of tetraethoxysilane, tetramethoxysilane, trimethoxy (3,3,3-trifluoropropyl) silane, methacryloxypropyl trimethoxy silane, dimethylmethoxy (3,3,3-trifluoropropyl) silane, phenyl silane, methoxytriphenyl silane, ethoxytriphenyl silane, dimethoxytetraphenyl disiloxane, diethoxytetraphenyl disiloxane or methoxyethoxytetraphenyl disiloxane.
[0015] In some of the embodiments, the mass ratio of the silicon-containing inorganic material to the organosilicon surfactant is (1-10): (1-30).
[0016] According to another aspect of the present application, an embodiment of the present application provides an electrolyte, wherein the electrolyte includes an electrolyte salt, an organic solvent, and an additive;
[0017] Wherein, the additive includes the electrolyte additive as mentioned above.
[0018] In some embodiments, the content of the electrolyte additive is 0.02% to 4% of the total mass of the electrolyte.
[0019] In some embodiments, the content of the silicon-containing inorganic material is 0.01% to 2% of the total mass of the electrolyte.
[0020] In some embodiments, the content of the organosilicon surfactant is 0.01% to 2% of the total mass of the electrolyte.
[0021] In some embodiments, the electrolyte salt includes an organic lithium salt and / or an inorganic lithium salt.
[0022] In some embodiments, the organic solvent includes an ester organic solvent and / or an ether organic solvent.
[0023] In some embodiments, the electrolyte salt includes at least one of LiPF6, LiFSI, LiTFSI, LiClO4, LiAsF6, LiBF4, LiPO2F2, LiDFOB or LiBOB.
[0024] In some embodiments, the concentration of the electrolyte salt is 1 to 3 mol / L.
[0025] In some embodiments, the organic solvent includes at least one of ethylene glycol dimethyl ether, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate or methyl propyl carbonate.
[0026] In some embodiments, the organic solvent includes at least one of propylene carbonate and ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate or methyl propyl carbonate.
[0027] According to another aspect of the present application, an embodiment of the present application provides a battery, wherein the battery includes the aforementioned electrolyte additive, or includes the aforementioned electrolyte.
[0028] Implementing the technical solution of the present invention has at least the following beneficial effects:
[0029] In the embodiment of the present application, the provided electrolyte additive includes a silicon-containing inorganic material and an organosilicon surfactant; wherein the organosilicon surfactant includes a hydrophilic group and a hydrophobic group; the electrolyte additive can be applied to an electrolyte, and the electrolyte containing the electrolyte additive can be applied to a battery, preferably to a lithium metal battery. Thus, by using an electrolyte additive containing both a silicon-containing inorganic material and an organosilicon surfactant, the hydrophilic group and the hydrophobic group simultaneously contained in the organosilicon surfactant can be used to reduce the surface tension of the silicon-containing inorganic material in the electrolyte, play a dispersing role, and improve the stability of the silicon-containing inorganic material in the electrolyte. At the same time, the silicon functional group in the organosilicon surfactant can react with lithium hydroxide (LiOH) on the surface of lithium metal, which can promote the formation of a stable SEI film; and the silicon-containing inorganic material can also react with lithium metal to form a layer of SEI film containing silicate on the surface of lithium metal, which can promote the uniform deposition of lithium ions, inhibit the generation of lithium dendrites, alleviate the lithium dendrite problem of existing lithium metal batteries, and improve the cycle performance of the battery.
[0030] Additional aspects and advantages of the present application will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION
[0031] The present application is further described below in conjunction with specific embodiments. It should be understood that these embodiments of the present application are only used to illustrate the present application and are not used to limit the scope of the present application.
[0032] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0033] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0034] As mentioned in the background technology, during the use of lithium metal batteries, the uneven deposition of lithium ions on the negative electrode of the lithium metal battery will cause the growth of lithium dendrites; the presence of lithium dendrites may deteriorate the battery performance, causing potential safety hazards in the battery or affecting the cycle life of the battery. The optimization of the electrolyte formula can inhibit lithium dendrites to a certain extent, and the optimization of the electrolyte formula is relatively simpler and easier to industrialize. In addition, usually, most electrolytes include fluoride-containing salts. Since the electrolyte and battery preparation process cannot completely remove water, hydrofluoric acid is easily generated in the fluoride-containing electrolyte, and hydrofluoric acid is easy to react with positive and negative electrode materials, which will affect the battery's electrical performance.
[0035] In view of this, the technical solution of the embodiment of the present application provides an electrolyte additive, which can be applied to the electrolyte, and the electrolyte can be applied to the battery, such as in a lithium metal battery. The technical solution of the embodiment of the present application uses a silicon-containing inorganic material that can react with hydrofluoric acid in the electrolyte as an electrolyte additive, and adds an organosilicon surfactant to promote the dispersion stability of the silicon-containing inorganic material in the electrolyte. The silicon-containing inorganic material and the organosilicon surfactant can react with the lithium metal negative electrode to form a stable SEI film on the surface of the lithium metal, inhibiting the occurrence of side reactions between the electrolyte and the lithium metal, stabilizing the lithium ion transmission, inhibiting the growth of lithium dendrites, and facilitating the realization of uniform lithium deposition, thereby facilitating the improvement of the cycle life and safety performance of the lithium metal battery. See below for a description of the specific technical solution.
[0036] In some embodiments, the present application provides an electrolyte additive, which includes a silicon-containing inorganic material and an organosilicon surfactant; wherein the organosilicon surfactant includes a hydrophilic group and a hydrophobic group.
[0037] In the embodiments of the present application, the provided electrolyte additive can be applied to an electrolyte, and the electrolyte containing the electrolyte additive can be applied to a battery, preferably a lithium metal battery. That is, the present application provides an electrolyte for a lithium metal battery, wherein the electrolyte contains the electrolyte additive of the present invention.
[0038] In this article, the term "electrolyte" refers to the carrier for ion transport in lithium batteries.
[0039] In this article, the term "additive or electrolyte additive" refers to a component with a smaller content in the electrolyte, which can be a gas, liquid or solid. Conceptually, the difference between electrolyte additives, organic solvents and lithium salts (or electrolyte salts) lies mainly in the different contents in the electrolyte.
[0040] In this document, the term "silicon-containing inorganic material" refers to an inorganic silicon material, that is, an inorganic material containing silicon element.
[0041] In this article, the term "organic silicone surfactant" refers to organosilicon materials, that is, a class of surfactants containing one or more organosilicon groups. Organosilicon surfactants can be divided into four categories according to the chemical properties of the hydrophilic groups in their chemical structure: anionic, cationic, nonionic and zwitterionic.
[0042] The organosilicon surfactant in the present application contains both a hydrophilic group (hydrophilic group) and a hydrophobic group (hydrophobic group).
[0043] Experiments show that the present application uses a composition including a silicon-containing inorganic material and a silicone surfactant as an electrolyte additive applied to the electrolyte. On the one hand, the silicon-containing inorganic material can react with the hydrofluoric acid in the electrolyte, thereby reducing the side reaction of the hydrofluoric acid in the electrolyte on the positive and negative electrode materials. Moreover, the silicon-containing inorganic material (such as silicon dioxide, etc.) can react with lithium metal to form a SEI film containing silicate on the surface of the lithium metal, wherein the silicate can act as an ion conductor to promote the transmission of lithium ions, promote the uniform deposition of lithium ions, inhibit the generation of lithium dendrites, and improve the cycle performance and safety performance of lithium metal batteries. On the other hand, silicone surfactants contain both hydrophilic groups and hydrophobic groups, which can reduce the surface tension of silicon-containing inorganic materials in the electrolyte, play a dispersing role, and improve the stability of silicon-containing inorganic materials in the electrolyte. At the same time, the silicon functional groups in the silicone surfactant can react with LiOH on the surface of lithium metal to form Li-O-Si chemical bonds, and their organic functional groups are reactive and compatible with the organic components in the lithium metal SEI film, thereby forming a stable SEI film, which is conducive to promoting the uniform deposition of lithium ions, alleviating the lithium dendrite problem of existing lithium metal batteries, and improving the cycle performance and safety performance of the battery.
[0044] It should be understood that in the related art, most of the methods of controlling the electrolyte solvent and the lithium salt water content are used to reduce the content of hydrofluoric acid in the electrolyte. This method can control the content of hydrofluoric acid in the electrolyte to a certain extent, but in the process of battery preparation, the moisture of the environment and the various materials and components of the assembled battery will inevitably introduce some moisture. If the control of each link is not strict, it is easy to cause excessive hydrofluoric acid in the electrolyte, which is easy to react with the battery material and affect the battery performance. Therefore, by adding a substance that can react with hydrofluoric acid to the electrolyte, the content of hydrofluoric acid in the electrolyte can be effectively suppressed. On the other hand, for the high activity of the lithium metal negative electrode of the lithium metal battery, it is easy to react spontaneously with the electrolyte to generate an unstable SEI film, which in turn affects the uneven deposition of lithium in the subsequent charge and discharge process, resulting in the continuous growth of lithium dendrites, affecting the cycle life of the battery. At present, it is usually used to modify a layer of artificial SEI film on the surface of lithium metal to promote the uniform deposition of lithium, but this method is complicated to operate and the uniformity is difficult to control. By adopting the method of the present invention, components dispersed in the electrolyte, that is, electrolyte additives dispersed in the electrolyte, react with lithium during the charging process to form a SEI film with high ionic conductivity on the surface of the lithium metal, thereby promoting uniform deposition of lithium and effectively alleviating the lithium dendrite problem of existing lithium metal batteries.
[0045] In some embodiments, the particle size of the silicon-containing inorganic material is nanometer-scale, that is, in the embodiments of the present application, the silicon-containing inorganic material is preferably an inorganic nano-silicon material, which is nanometer-scale silicon particles.
[0046] Inorganic nano-silicon materials are used in electrolyte additives, which have the characteristics of high purity, small particle size, uniform distribution, etc. In addition, they also have the characteristics of large surface area, high surface activity and low bulk density.
[0047] In some embodiments, the particle size of the silicon-containing inorganic material ranges from 5 nm to 50 nm. As an example, the particle size of the silicon-containing inorganic material can be 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, or a range consisting of any two of the above values.
[0048] By controlling the particle size of the silicon-containing inorganic material within the above range, it is not only easy to prepare and can reduce production costs, but also has a small particle size and uniform distribution. Applying the inorganic nano-silicon material within this particle size range in the electrolyte can achieve better results, such as being easier to evenly and stably disperse in the electrolyte.
[0049] In some embodiments, the silicon-containing inorganic material includes, but is not limited to, at least one of nano glass powder, nano silicon dioxide, nano silicon oxide, nano silicon element, or nano silicon carbide.
[0050] Preferably, the silicon-containing inorganic material is selected from any one of nano glass powder, nano silicon dioxide, nano silicon oxide or nano silicon element or a mixture of at least two of them in any proportion.
[0051] By selecting the above-mentioned nano-inorganic silicon materials, not only can they react with the hydrofluoric acid in the electrolyte to reduce the side reaction of the hydrofluoric acid in the electrolyte on the positive and negative electrode materials, but also the nano-inorganic silicon materials such as silicon dioxide can react with lithium metal to form a SEI film containing silicate on the surface of lithium metal, in which silicate can act as an ion conductor to promote the transmission of lithium ions, promote the uniform deposition of lithium ions, and inhibit the formation of lithium dendrites, thereby improving the cycle performance and safety performance of the battery.
[0052] In some embodiments, the hydrophilic group is a group containing a CO bond, and the hydrophobic group is a group containing a silicon-oxygen bond. For example, the hydrophilic group may include a CO bond and an organic hydrocarbon connected thereto, and the hydrophobic group may include a silicon-oxygen bond and an organic hydrocarbon connected thereto.
[0053] It should be noted that the present application does not limit the specific type of organic hydrocarbon connected to the CO bond or the silicon-oxygen bond, and it can be selected and set according to actual conditions.
[0054] In the present application, the selected organosilicon surfactant should contain a high polarity portion that can combine with the silicon-containing inorganic material and a low polarity portion that can combine with the solvent in the electrolyte.
[0055] In some embodiments, the silicone surfactant includes, but is not limited to, any one of tetraethoxysilane, tetramethoxysilane, trimethoxy (3,3,3-trifluoropropyl) silane, methacryloxypropyl trimethoxy silane, dimethylmethoxy (3,3,3-trifluoropropyl) silane, phenyl silane, methoxytriphenyl silane, ethoxytriphenyl silane, dimethoxytetraphenyl disiloxane, diethoxytetraphenyl disiloxane or methoxyethoxytetraphenyl disiloxane, or a combination of at least two thereof. For the sake of brevity, the combinations within the above range are not listed one by one.
[0056] Therefore, by selecting the above-mentioned tetraethoxysilane, tetramethoxysilane and other organosilicon surfactants, which contain both a high-polarity part that can combine with silicon-containing inorganic materials and a low-polarity part that can combine with the solvent in the electrolyte, it is beneficial to improve the stability of the electrolyte system, and can also react with LiOH on the surface of lithium metal to form Li-O-Si chemical bonds. Its organic functional groups are reactive and compatible with the organic components in the lithium metal SEI film, thereby forming a stable SEI film.
[0057] In the present application, the mass ratio of the silicon-containing inorganic material and the organosilicon surfactant may affect the uniformity or stability of the electrolyte system, or may affect the film-forming effect of the electrode interface, the impedance of the electrode interface, etc., and ultimately affect the cycle performance or safety performance of the battery.
[0058] In some embodiments, the mass ratio of the silicon-containing inorganic material to the organosilicon surfactant is (1-10):(1-30). As an example, the mass ratio of the silicon-containing inorganic material to the organosilicon surfactant can be 1:2, 1:4, 1:10, 1:30, 5:2, 5:1, 10:1, 8:1, etc.
[0059] By keeping the mass ratio of the silicon-containing inorganic material to the silicone surfactant within the above range, it can be ensured that the silicon-containing inorganic material can be evenly and stably distributed in the electrolyte to form a homogeneous phase, which is beneficial to improving the uniformity or stability of the electrolyte system, and helps to reduce the amount of electrolyte additives in the electrolyte to avoid deterioration of the electrolyte conductivity; a dense, stable and uniform interface film can be formed at the electrode interface to effectively inhibit side reactions.
[0060] Therefore, the present invention adopts an electrolyte additive including a silicon-containing inorganic material and an organosilicon surfactant, and can utilize the hydrophilic groups and hydrophobic groups simultaneously contained in the organosilicon surfactant to reduce the surface tension of the silicon-containing inorganic material in the electrolyte, thereby playing a dispersing role and improving the stability of the silicon-containing inorganic material in the electrolyte. At the same time, the silicon functional group in the organosilicon surfactant can react with lithium hydroxide (LiOH) on the surface of lithium metal to promote the formation of a stable SEI film; and the silicon-containing inorganic material can also react with lithium metal to form a layer of SEI film containing silicate on the surface of lithium metal, thereby promoting the uniform deposition of lithium ions, inhibiting the generation of lithium dendrites, alleviating the lithium dendrite problem of existing lithium metal batteries, improving the cycle performance of the battery, and also improving the safety performance of the battery.
[0061] In some embodiments, the present application provides an electrolyte comprising an electrolyte salt, an organic solvent and an additive; wherein the additive comprises the electrolyte additive as described above.
[0062] It should be understood that the electrolyte includes the aforementioned electrolyte additives, and therefore, all the features and advantages described above for the "electrolyte additives" are also applicable to the "electrolyte" and will not be described in detail here.
[0063] By controlling the mass content of electrolyte additives in the electrolyte within a suitable range, such as controlling the mass content of silicon-containing inorganic materials and organosilicon surfactants within a suitable range, the electrolyte can enable the battery to have excellent rate performance as well as good cycle performance and safety performance.
[0064] In some embodiments, the content of the electrolyte additive is 0.02% to 4% of the total mass of the electrolyte, and can further be 0.05% to 3%. For example, it includes but is not limited to 0.02%, 0.04%, 0.08%, 0.1%, 0.2%, 0.5%, 0.8%, 1%, 1.5%, 2%, 3%, 4%, including any value and all ranges and sub-ranges therein.
[0065] In some embodiments, the content of the silicon-containing inorganic material is 0.01% to 2% of the total mass of the electrolyte, and can further be 0.05% to 1.5%, including but not limited to 0.01%, 0.02%, 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, including any value and all ranges and sub-ranges therein.
[0066] In some embodiments, the content of the organosilicon surfactant is 0.01% to 2% of the total mass of the electrolyte, and can further be 0.05% to 1.5%, including but not limited to 0.01%, 0.02%, 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, including any value and all ranges and sub-ranges therein.
[0067] By controlling the mass content of silicon-containing inorganic materials and silicone surfactants in the electrolyte within the above range, it is beneficial to improve the uniformity or stability of the electrolyte system, and it helps to reduce the amount of electrolyte additives in the electrolyte and avoid the deterioration of the electrolyte conductivity; a dense, stable and uniform interface film can be formed at the electrode interface, effectively inhibiting side reactions and alleviating the formation of lithium dendrites, so that the battery containing the electrolyte can have excellent rate performance as well as good cycle performance and safety performance.
[0068] The electrolyte lithium salt used in the present application is not specifically limited and can be appropriately selected according to actual needs, as long as the technical solution of the present application can be achieved. In some embodiments, the electrolyte salt includes an organic lithium salt and / or an inorganic lithium salt. That is, in the embodiments of the present application, the electrolyte lithium salt can be selected from one or more of an organic lithium salt and an inorganic lithium salt.
[0069] For example, in some embodiments, the electrolyte salt includes, but is not limited to, any one or a combination of at least two of LiPF6 (lithium hexafluorophosphate), LiTFSI (lithium bistrifluorosulfonyl imide), LiFSI (lithium bisfluorosulfonyl imide), LiClO4, LiAsF6, LiBF4, LiPO2F2, LiDFOB or LiBOB. For the sake of brevity, the combinations within the above range are no longer listed one by one.
[0070] In some embodiments, the concentration of the electrolyte salt is 1 to 3 mol / L, preferably 1 to 2 mol / L, including but not limited to 0.5 mol / L, 1.0 mol / L, 1.2 mol / L, 1.5 mol / L, 1.8 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, including any values and all ranges and sub-ranges therein.
[0071] There is no specific restriction on the type of organic solvent used in the present application, and it can be appropriately selected according to actual needs, as long as the technical solution of the present application can be realized. As an example, in the embodiment of the present application, the organic solvent can be selected from at least one of carbonate, carboxylate, sulfate, phosphate, amide, nitrile or ether. For example, including but not limited to, the organic solvent can be selected from ester organic solvent, ether organic solvent or a mixture of ester organic solvent and ether organic solvent.
[0072] Illustratively, in some embodiments, the organic solvent includes, but is not limited to, one or more of ethylene glycol dimethyl ether, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, or methyl propyl carbonate.
[0073] In other embodiments, the organic solvent includes, but is not limited to, one or more of propylene carbonate and ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, or methyl propyl carbonate.
[0074] In addition, in other embodiments, the organic solvent machine can also select one or more of acetonitrile, cyclopentane sulfoxide, dimethyl sulfoxide, ethylene sulfite, propylene sulfite, triethyl phosphate, methyl ethyl phosphite, fluorine-containing cyclic organic esters, sulfur-containing cyclic organic esters, etc. known in the art.
[0075] The organic solvent may be a mixed solvent of two or more of the above organic solvents, and their ratio is not particularly limited and can be appropriately selected according to actual needs, as long as the technical solution of the present application can be achieved. For example, in an embodiment of the present application, when the organic solvent includes two different organic solvents, they can be mixed and used in a volume ratio of 1:1, 2:8, 3:7, 4:6, 8:2, 7:3, 6:4, etc.
[0076] The content of the above-mentioned organic solvent in the electrolyte is not specifically limited and can be appropriately selected according to actual needs, as long as the technical solution of the present application can be realized. As an example, in an embodiment of the present application, the content of the organic solvent in the electrolyte can be 50wt% to 90wt%, and further can be 70wt% to 80wt%. For example, including but not limited to 50%, 55%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, etc., including any value and all ranges and sub-ranges therein.
[0077] In addition, as an improvement to the electrolyte of the present application, other functional additives known in the art that can be used to improve the performance of lithium batteries may be added to the electrolyte, such as flame retardant additives, anti-overcharge additives, conductive additives and other functional additives, which will not be repeated here.
[0078] Optionally, the electrolyte of the present application can be prepared by a method known in the art. As an example, the preparation of the electrolyte includes the following steps: first preparing a basic electrolyte, the basic electrolyte including an organic solvent and an electrolyte salt (such as a lithium salt); then adding a nano-scale silicon-containing inorganic material and an organic silicon surfactant to the above-mentioned basic electrolyte, and uniformly dispersing the silicon-containing inorganic material in the electrolyte by ultrasonic method to obtain a homogeneous suspension.
[0079] In some embodiments, the present application provides a battery comprising the aforementioned electrolyte additive, or comprising the aforementioned electrolyte.
[0080] Preferably, the above-mentioned battery is a lithium metal battery.
[0081] The battery provided in the present application, such as a lithium metal battery, includes a positive electrode plate, a separator, a negative electrode plate, and an electrolyte in any embodiment.
[0082] Optionally, the negative electrode plate may be a negative electrode plate containing metallic lithium, such as a metallic lithium plate, or a copper-lithium plate, or a negative electrode plate obtained by combining metallic lithium with other functional layers.
[0083] Optionally, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector and including a positive electrode active material. For example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.
[0084] There is no specific limitation on the type of positive electrode current collector used in the positive electrode sheet of the present application, and it can be appropriately selected according to actual needs, as long as the technical solution of the present application can be realized. As an example, the positive electrode current collector can be selected from aluminum, nickel, titanium, stainless steel, carbon, aluminum sheets coated with nickel or titanium, and stainless steel sheets coated with nickel or titanium.
[0085] There is no specific restriction on the type of positive electrode active material used in the positive electrode plate of the present application, and it can be appropriately selected according to actual needs, as long as the technical solution of the present application can be realized. As an example, the positive electrode active material can be selected from one or more of lithium-containing layered metal oxides, lithium-free metal oxides, spinel-structured lithium metal oxides, lithium metal phosphates, lithium metal fluoride sulfates, and lithium metal vanadates. Exemplarily, the positive electrode active material includes, but is not limited to, lithium cobalt oxide (LCO), nickel cobalt manganese ternary material (NMC), nickel cobalt aluminum oxide (NCA), lithium manganese oxide (LiMn2O4), lithium iron phosphate (LFP), etc.
[0086] Optionally, the positive electrode film layer may further include a conductive agent and a binder. The present application does not limit the specific types of the conductive agent and the binder, and any type or component known in the art that can be used in a positive electrode sheet of a battery may be selected.
[0087] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0088] 1. Preparation of batteries
[0089] Example 1
[0090] (1) Preparation of electrolyte
[0091] Providing a basic electrolyte, wherein the organic solvent in the basic electrolyte is ethylene carbonate (EC) and dimethyl carbonate (DMC), and the electrolyte salt is lithium hexafluorophosphate (LiPF6);
[0092] To a basic electrolyte of LiPF6 (concentration 1 mol / L) of EC and DMC (the volume ratio of EC and DMC is 1:1), 0.05% and 0.2% by mass of nano-silicon dioxide (average particle size 10 nm) and tetraethoxysilane were added, and the mixture was magnetically stirred at a speed of 500 r / min for 10 h. After mixing evenly, an electrolyte was obtained.
[0093] (2) Preparation of positive electrode sheet
[0094] The positive electrode active material ternary material NCM613, the conductive agent conductive carbon black (Super P) and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 96:2:2, dispersed in N-methylpyrrolidone (NMP) solvent, and stirred evenly to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and dried at 80°C for 12 hours to form a positive electrode active material layer; then it is pressed and cut into 3cm×4cm as a positive electrode sheet.
[0095] (3) Preparation of negative electrode sheet
[0096] The 50 μm copper-lithium tape was cut into 3.4 cm × 4.4 cm pieces using a cutting machine to serve as the negative electrode.
[0097] (4) Isolation film
[0098] A 4 cm×5 cm Celgard 2023 membrane (polypropylene-polyethylene-polypropylene three-layer membrane) was used as the isolation membrane.
[0099] (5) Preparation of batteries
[0100] After the positive electrode sheet and the negative electrode sheet of Example 1 are welded to the electrode ears by an ultrasonic welding machine, the positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is located between the positive and negative electrode sheets to isolate the positive and negative electrodes. Then, they are placed in an outer packaging aluminum-plastic film, and the prepared electrolyte is injected into the dried battery cell. After vacuum sealing, standing, formation and other processes, a battery (lithium metal battery) is obtained.
[0101] In Examples 2 to 9, the amount of electrolyte additives in the electrolyte is adjusted (Examples 2 to 5 mainly adjust the amount of silicon-containing inorganic materials, and Examples 6 to 9 mainly adjust the amount of silicone surfactants), and other parameters remain basically the same as in Example 1. The specific parameters are shown in Table 1.
[0102] In Examples 10 to 13, the types of components in the electrolyte additives in the entire electrolyte are adjusted (Examples 10 to 11 mainly adjust the types of silicon-containing inorganic materials, and Examples 12 to 13 mainly adjust the types of silicone surfactants), and other parameters remain basically the same as in Example 1. The specific parameters are shown in Table 1.
[0103] In Example 14, the types of electrolyte salt and organic solvent in the basic electrolyte were adjusted, and other parameters remained basically the same as in Example 1. The specific parameters are shown in Table 1.
[0104] In Comparative Examples 1 to 3, the composition of the electrolyte was adjusted so that the electrolyte did not contain electrolyte additives, or only included one of the silicon-containing inorganic material and the organosilicon surfactant. The other parameters were basically the same as those in Example 1. The specific parameters are shown in Table 1.
[0105] In Comparative Examples 4 to 6, the composition of the electrolyte was adjusted so that the electrolyte did not contain electrolyte additives, or only included one of the silicon-containing inorganic material and the organosilicon surfactant. The other parameters remained basically the same as those in Example 14. The specific parameters are shown in Table 1.
[0106] Table 1
[0107]
[0108]
[0109] Note: In Table 1, “ / ” means not added.
[0110] 2. Test Method
[0111] (1) Hydrofluoric acid content test: Use an electrochemical tester to measure the current signal of hydrofluoric acid in the electrolyte to obtain the hydrofluoric acid (HF) content.
[0112] (2) Conductivity (25°C) test: The conductivity of the lithium-ion battery electrolyte is measured using the electrical impedance spectroscopy (EIS) method. By applying small alternating current signals of different frequencies, the characteristics of the electrochemical reaction in the lithium battery system are measured to obtain the electrolyte conductivity.
[0113] (3) Cycle performance (capacity retention rate after 100 cycles) test: At 25°C, charge to 4.3V at a constant current density of 0.2C, and record the charge capacity at this time as the first charge capacity; then discharge to 3.0V at a constant current density of 0.5C, and record the discharge capacity at this time as the first discharge capacity. Repeat the above charge and discharge cycle for 100 cycles, and record the discharge capacity at the 100th cycle; the capacity retention rate after 100 cycles can be calculated by the following formula:
[0114] Capacity retention rate at the 100th cycle = discharge capacity at the 100th cycle / first discharge capacity*100%.
[0115] (4) Rate performance (discharge capacity retention rate at different rates at 25°C) test: At 25°C, charge to 4.3V at 0.2C rate, and continue to discharge to 3.0V at 0.2C rate for 5 cycles to obtain a stable capacity, and record the discharge capacity at this time as the 0.2C discharge capacity; then charge to 4.3V at 0.2C rate, and continue to discharge to 3.0V at a large rate of XC (X=0.5, 1, 2, 3), and also cycle for 5 cycles to obtain a stable capacity, and record the discharge capacity at this time as the XC (X=0.5, 1, 2, 3) discharge capacity, then the XC (X=0.5, 1, 2, 3) discharge capacity retention rate = XC (X=0.5, 1, 2, 3) discharge capacity / 0.2C discharge capacity*100%.
[0116] The above hydrofluoric acid content test and conductivity test results are shown in Table 2 below.
[0117] The results of the above cycle performance test and rate performance test are shown in Table 3 below.
[0118] III. Analysis of test results of various embodiments and comparative examples
[0119] Table 2
[0120] Group Hydrofluoric acid content (mg / kg) <![CDATA[Conductivity at 25 °C (g / cm 3 )]]> Example 1 37.5 15.7 Example 2 34.2 15.4 Example 3 26.5 14.5 Example 4 26.1 13.2 Example 5 25.8 12.9 Example 6 38.6 15.9 Example 7 37.9 15.5 Example 8 37.3 15.2 Example 9 37.5 14.9 Example 10 38.2 15.6 Embodiment 11 38.2 15.8 Example 12 36.2 15.4 Embodiment 13 36.7 15.5 Embodiment 14 37.1 14.5 Comparative Example 1 73.6 16.7 Comparative Example 2 42.5 15.4 Comparative Example 3 70.8 14.9 Comparative Example 4 50.3 15.2 Comparative Example 5 32.1 14.9 Comparative Example 6 48.4 14.8
[0121] Table 3
[0122]
[0123]
[0124] It can be seen from the data in Table 2 and Table 3 above that, in general, compared with Comparative Examples 1 to 6, the batteries using the electrolytes of Examples 1 to 14 of the present invention can reduce the hydrofluoric acid (HF) content to a certain extent, improve the conductivity, and also improve the rate performance and cycle performance of the battery due to the addition of the electrolyte additive provided by the present application to the electrolyte.
[0125] In addition, it can be seen from the data in Table 2 that with the increase in the amount of electrolyte additives, the HF content will decrease, indicating that the added nano-silicon dioxide can react with the hydrofluoric acid powder in the electrolyte to reduce its HF content; in addition, with the increase in the content of nano-silicon dioxide, its conductivity decreases. This shows that the electrolyte additive composed of silicon-containing inorganic materials and silicone surfactants will increase the viscosity of the electrolyte, resulting in a decrease in the conductivity of the electrolyte. The more the amount added, the greater the viscosity of the electrolyte and the lower the conductivity. In addition, the addition of silicon-containing inorganic materials will reduce the HF content in the electrolyte, and is also affected by the amount of silicone surfactant added, because silicone surfactants can improve the dispersibility of inorganic silicon materials in the electrolyte and improve the stability of the electrolyte. When the ratio of silicon-containing inorganic materials to silicone surfactants is 5:2, it can have good dispersibility. Therefore, with the addition of more silicon-containing inorganic materials and the matching of an appropriate amount of silicone surfactants, the HF content in the electrolyte will be lower.
[0126] It can also be seen from the data in Table 3 that the organosilicon surfactant will spontaneously form a stable SEI film on the surface of lithium metal, improving the stability of lithium metal during the cycle. When the content of silicon-containing inorganic material is 0.5% and the mass ratio of silicon-containing inorganic material to organosilicon surfactant is 5:2, the rate performance and cycle performance of the prepared battery are optimal, while the rate and cycle performance of the electrolyte without additives in the comparative example are the worst, indicating that an appropriate amount of nano-silicon dioxide can reduce the content of hydrofluoric acid in the battery, promote the uniform deposition of lithium, and improve its rate and cycle performance. However, adding too much nano-silicon dioxide will reduce the conductivity of the electrolyte, reduce the ion migration speed, increase the battery polarization, and reduce the rate and cycle performance of the battery. In addition, the rate performance and cycle performance of the electrolyte without adding organosilicon surfactant in the comparative example are reduced because the organosilicon surfactant can improve the stability of the electrolyte and the stability and conductivity of SEI at the same time.
[0127] Furthermore, by adjusting the content of silicon-containing inorganic materials and organosilicon surfactants, the HF content and conductivity in the electrolyte are changed, which affects the kinetic performance and cycle performance of the battery, thereby improving the battery's rate and cycle performance.
[0128] Parts of the present invention that are not described in detail are well known to those skilled in the art.
[0129] The basic principle of the present invention is described above in conjunction with specific embodiments. However, it should be pointed out that the advantages, strengths, effects, etc. mentioned in the present invention are only examples and not limitations, and it cannot be considered that these advantages, strengths, effects, etc. must be possessed by each embodiment of the present invention. In addition, the specific details disclosed above are only for the purpose of illustration and facilitation of understanding, rather than limitation, and the above details do not limit the present invention to being implemented by adopting the above specific details.
[0130] It should be noted that the term "and / or" or " / " used in this document is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The singular forms of "a", "the" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0131] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0132] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An electrolyte additive, characterized in that: Including silicon-containing inorganic materials and silicone surfactants; The organosilicon surfactant includes a hydrophilic group and a hydrophobic group.
2. The electrolyte additive according to claim 1, characterized in that: The particle size of the silicon-containing inorganic material is in the range of 5 nm to 50 nm; and / or, The silicon-containing inorganic material includes at least one of nano glass powder, nano silicon dioxide, nano silicon oxide, nano silicon element or nano silicon carbide.
3. The electrolyte additive according to claim 1, characterized in that: The hydrophilic group is a group containing a CO bond, and the hydrophobic group is a group containing a silicon-oxygen bond; Preferably, the silicone surfactant includes at least one of tetraethoxysilane, tetramethoxysilane, trimethoxy (3,3,3-trifluoropropyl) silane, methacryloxypropyl trimethoxy silane, dimethylmethoxy (3,3,3-trifluoropropyl) silane, phenyl silane, methoxytriphenyl silane, ethoxytriphenyl silane, dimethoxytetraphenyl disiloxane, diethoxytetraphenyl disiloxane or methoxyethoxytetraphenyl disiloxane.
4. The electrolyte additive according to any one of claims 1 to 3, characterized in that: The mass ratio of the silicon-containing inorganic material to the organic silicon surfactant is (1-10):(1-30).
5. An electrolyte, characterized in that: The electrolyte comprises an electrolyte salt, an organic solvent and an additive; Wherein, the additive comprises the electrolyte additive according to any one of claims 1 to 4.
6. The electrolyte according to claim 5, characterized in that The content of the electrolyte additive is 0.02% to 4% of the total mass of the electrolyte; Preferably, the content of the silicon-containing inorganic material is 0.01% to 2% of the total mass of the electrolyte; Preferably, the content of the organosilicon surfactant is 0.01% to 2% of the total mass of the electrolyte.
7. The electrolyte according to claim 5 or 6, characterized in that The electrolyte salt comprises an organic lithium salt and / or an inorganic lithium salt; and / or, The organic solvent includes an ester organic solvent and / or an ether organic solvent.
8. The electrolyte according to claim 7, characterized in that The electrolyte salt includes at least one of LiPF6, LiFSI, LiTFSI, LiClO4, LiAsF6, LiBF4, LiPO2F2, LiDFOB or LiBOB; Preferably, the concentration of the electrolyte salt is 1 to 3 mol / L.
9. The electrolyte according to claim 7, characterized in that The organic solvent comprises at least one of ethylene glycol dimethyl ether, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate or methyl propyl carbonate; Alternatively, the organic solvent includes at least one of propylene carbonate and ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate or methyl propyl carbonate.
10. A battery, characterized in that: The battery comprises the electrolyte additive according to any one of claims 1 to 4, or comprises the electrolyte according to any one of claims 5 to 9.
Citation Information
Patent Citations
Electrolyte containing inorganic additive and lithium-ion battery containing electrolyte
CN105938919A
Multifunctional composite electrolyte additive
CN113206297A
High-safety electrolyte and preparation method thereof
CN113903994A
Lithium battery electrolyte preparation process
CN115882068A
Lithium ion battery cell comprises components, which contain inorganic multifunctional component having a low thermal conductivity, where the inorganic multifunctional component has a reciprocal of the thermal diffusivity
DE102010013294A1
Cited By
Electrolyte and lithium ion battery
CN121307199A